On encrusted soil and mud: A preliminary phylogenetic analysis of the mud spider family Paratropididae Simon, 1889 (Araneae: Mygalomorphae) brings to light new species and genera - Pedro Peñaherrera, R. (2025)
We present the first exploratory morphological phylogeny of the spider family Paratropididae Simon, 1889, offering a critical re-evaluation of its internal systematics. Our analysis reveals seven distinct lineages, recognised here as putative genera, three of which are newly described from Ecuador and Guyana. This study underscores the previously overlooked diagnostic value of both somatic and genitalic characters in genus-level delimitation within the family. In addition to a revised concept of Paratropis Simon, 1889, we describe 11 new species based on detailed genital morphology. Two species, Paratropis pasochoa Dupérré et Tapia, 2024 and Anisaspis awa Sherwood, Brescovit et Lucas, 2023, are transferred to the new genus Alienus gen.n., forming the new combinations Alienus pasochoa comb.n. and Alienus awa comb.n., based on topotypic and type material and their phylogenetic placement. Stormtropis celiae (Santos, Gomes, Almeida, de Morais et Bertani, 2025) comb.n. and Stormtropis manauara (Santos, Gomes, Almeida, de Morais et Bertani, 2025) comb.n. are transferred to Stormtropis from their previously incorrect placement in Paratropis. We further propose Anisaspis Simon, 1892 and its type species A. tuberculata as nomina dubia due to the absence of diagnostic adult material. Our findings highlight the importance of using robust morphological datasets to recover natural groups, providing a refined framework for future studies. Additionally, we report the first occurrences of Stormtropis Perafán, Galvis et Pérez-Miles, 2019 from Venezuela, describe the first species and a new endemic genus (Yamaratropis gen.n.) from an Andean Tepui, and document novel behaviours, including burrow construction and the use of anthropogenic materials (e.g., microplastics). The discovery of burrowing behaviour in several species offers new insight into the behavioural evolution of early Bipectina, suggesting a basal origin for open burrow entrance types. This work establishes a critical morphological baseline for future integrative research.